Seeding the World - Alvarez, Rafael (Journal of Agriculture, Food Systems, and Community Development, 2020)
First paragraphs: Debra Williby-Walker has a great story to tell, and it’s living under her roof in Mercer County, West Virginia. With her is eight-year-old Brady, her charismatic grandson, who has given away more than 6,000 packets of vegetable seeds to families around the world. Williby-Walker, 52, and Brady live in Oakvale, population fewer than 125, just a few miles west of a mountain range separating the Mountain State from far southern Virginia. “Brady learned to plant seeds around the age of two or three from his Poppy, my Dad, who has two big gardens that connect to my property. One is just for potatoes, and the other? My mom cans everything they grow. They feed all of us in the family." . . .